2006
DOI: 10.1021/cm060883e
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Vapor Deposition of Zirconium Oxide on Aerosolized Silicon Nanoparticles

Abstract: Nanoscale shells of ZrO2 were deposited onto size-selected, aerosolized Si nanoparticles by chemical vapor deposition (CVD). The CVD precursor was nitronium pentanitratozirconate (ZN, [NO2][Zr(NO3)5]), which has been used previously to deposit ZrO2 films on silicon wafers. Silicon nanocrystals were synthesized from silane in a low-pressure nonthermal plasma and were directly extracted from the plasma growth chamber into an atmospheric-pressure aerosol flow tube reactor. The particle streams flowed first throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Particle sizing instruments have recently been used in novel ways to investigate Si nanoparticle surfaces. Roberts and co-workers have shown that the surface chemistry of Si nanoparticles can be investigated. Surface chemistry ranging from measuring the desorption of a monolayer of hydrogen atoms from Si nanoparticles to oxidation kinetics of Si nanoparticles, chemical vapor deposition, and self-assembly of organic monolayers was investigated …”
Section: Examples Of Some Of the Experimental Methods Used To Investi...mentioning
confidence: 99%
“…Particle sizing instruments have recently been used in novel ways to investigate Si nanoparticle surfaces. Roberts and co-workers have shown that the surface chemistry of Si nanoparticles can be investigated. Surface chemistry ranging from measuring the desorption of a monolayer of hydrogen atoms from Si nanoparticles to oxidation kinetics of Si nanoparticles, chemical vapor deposition, and self-assembly of organic monolayers was investigated …”
Section: Examples Of Some Of the Experimental Methods Used To Investi...mentioning
confidence: 99%
“…As a result, there is interest in developing gas-phase coating and functionalization processes that can occur before particle collection (Figure 2). Freshly aerosol-made TiO 2 , Fe 2 O 3 , Si, and Ag particles have been coated in situ with nanothin SiO 2 (56) or ZrO 2 shells (57) in sequential aerosol processes. The hermetic and smooth or granular texture of such shells is important for their applications (55).…”
Section: Process Overviewmentioning
confidence: 99%
“…The subject of this paper is a novel non-thermal plasma method, which offers an all-gasphase approach to the synthesis and surface functionalization of silicon nanocrystals, which readily disperse in organic solvents to form stable silicon ink. Roberts and co-workers [18,19] first demonstrated that gas phase surface functionalization of silicon nanocrystals can avoid a lot of the inconveniences of liquid phase treatment. In ref.…”
mentioning
confidence: 99%